Discussion: How Different Can Perspectives on L2 Development Be?. Issue 1 (March 2015) - Hulstijn, Jan H.; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> In this article I discuss the contributions to this Special Issue of Language Learning on orders and sequences in second language (L2) development. Using a list of questions, I attempt to characterize what I see as the strengths, limitations, and unresolved issues in the approaches to L2 development represented in this Special Issue. I include short commentaries I solicited from the authors of the contributions, cited as personal communications. I conclude by arguing that, while it is completely legitimate to focus research and theory construction on the first few behavioral signs of acquisition of target structures (called emergence), there should also be room for research that looks at the entire developmental trajectory for a given set of related structures, from emergence to full mastery, to be examined in relevant target populations (differing in first language, differing in explicit knowledge), using several elicitation tasks, to be administered many times over the period that it takes to reach full mastery of all structures under investigation. Arguably, if such studies are to yield nontrivial findings, second language acquisition researchers should do their best to construct theories explaining these findings.